Impact of shamba shape up and iShamba on livestock and climate resilience - Vyas, Shalika; Burra, Dharani Dhar; Calvin, Kiprop; Kirwa, Lilian; Rottmann, Sophie; Ramirez Villegas, Julian (2024)
This report assesses the impact of Shamba Shape Up (SSU) and iShamba advisory services on smallholder farmers in Kenya, focusing on livestock productivity, climate adaptation, and financial literacy. Data from surveys conducted in 2023 and 2024 highlight the effectiveness of these advisories in improving farming practices, economic outcomes, and resilience.